2016
DOI: 10.1371/journal.pone.0162628
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Peroxisome Proliferator-Activated Receptor Alpha Improves Aged and UV-Irradiated Skin by Catalase Induction

Abstract: Peroxisome proliferator-activated receptor alpha (PPARα) is a nuclear hormone receptor involved in the transcriptional regulation of lipid metabolism, fatty acid oxidation, and glucose homeostasis. Its activation stimulates antioxidant enzymes such as catalase, whose expression is decreased in aged human skin. Here we investigated the expression of PPARα in aged and ultraviolet (UV)-irradiated skin, and whether PPARα activation can modulate expressions of matrix metalloproteinase (MMP)-1 and procollagen throug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 49 publications
0
26
0
Order By: Relevance
“…We believe targeting PPAR α to be important in targeting conspicuous pores and age spots as levels of its mRNA are diminished in photodamaged skin . Moreover, its levels were diminished in irradiated fibroblasts.…”
Section: Discussionmentioning
confidence: 93%
“…We believe targeting PPAR α to be important in targeting conspicuous pores and age spots as levels of its mRNA are diminished in photodamaged skin . Moreover, its levels were diminished in irradiated fibroblasts.…”
Section: Discussionmentioning
confidence: 93%
“…Catalase cleaves hydrogen peroxide to oxygen and water . Catalase overexpression in keratinocytes reduces apoptosis and MMP‐1 expression . GSH reduces hydrogen peroxide and lipid radicals formed during oxidative stress, contributing to reduction of the MMP‐1 level that is enhanced by UV‐B irradiation .…”
Section: Discussionmentioning
confidence: 99%
“…28 Catalase overexpression in keratinocytes reduces apoptosis and MMP-1 expression. 29,30 GSH reduces hydrogen peroxide and lipid radicals formed during oxidative stress, contributing to reduction of the MMP-1 level that is enhanced by UV-B irradiation. 31,32 We found that UV-B exposure significantly reduced both GSH and catalase levels;…”
Section: Bbe Inhibits Uv-b-induced Ros Generation In Keratinocytesmentioning
confidence: 99%
“…Catalase breaks down hydrogen peroxide, rendering it nontoxic [17]. The overexpression of catalase was shown to protect keratinocytes by decreasing intracellular ROS, inhibiting apoptosis in keratinocytes [18], and reducing MMP-1 levels in dermal fibroblasts [19]. GSH reduces oxidative molecules, including hydrogen peroxides and lipid radicals, by acting as an electron donor, which results in its conversion to GSSG.…”
Section: Discussionmentioning
confidence: 99%